Syphilitic Hepatitis in Infancy Presenting with Cholestatic Jaundice and Inguinal Hernia: A Case Report - Diva Putra, Agus Indra Yudhistira; Putu, Pradnyanita Mustika; Anak Agung, Made Sucipta (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Congenital syphilis can involve multiple organ systems and, in rare cases, present with syphilitic hepatitis, a cause of cholestatic jaundice in infancy. Early recognition is challenging due to its non-specific presentation and overlap with other etiologies of neonatal cholestasis. This case highlights a rare case of a cholestatic infant with syphilitic hepatitis and concurrent inguinal hernia, emphasizing diagnostic challenges and management in resource-limited settings. Case: A 1-month-26-day-old infant presented with a left inguinal mass and jaundice. The mother had latent syphilis during pregnancy and received benzathine penicillin G only one week before delivery. The infant had persistent jaundice, pale stools, elevated direct bilirubin, transaminases, and alkaline phosphatase. Abdominal ultrasonography showed normal liver echotexture and gallbladder contractility, with no biliary dilatation. Based on clinical, laboratory, and maternal history, a presumptive diagnosis of biliary atresia with differential syphilitic hepatitis was made. Supportive therapy with ursodeoxycholic acid, fat-soluble vitamins, and antibiotics was initiated. The patient was referred for further evaluation by pediatric gastroenterohepatology. Discussion: The infant presented with postnatal jaundice, acholic stools, and elevated indirect bilirubin, initially raising suspicion of biliary atresia. However, the maternal history was positive for syphilis, making syphilitic hepatitis a presumptive diagnosis. Careful clinical evaluation and close serial follow-up are essential for establishing the diagnosis and guiding management. Early antenatal screening and timely maternal treatment remain key strategies to prevent vertical transmission. Conclusion: Syphilitic hepatitis should be considered in the differential diagnosis of neonatal cholestasis, particularly in infants born to mothers with inadequately treated syphilis.